The “dark” side of terlipressin: a case report of ischemic skin necrosis and review of literature - Arpit Shastri; Sweta Rose; Nikhil Vojjala; Naveen Bhagat; Arka De (Egyptian Liver Journal, 2023)
Abstract Background Terlipressin is a commonly used drug in cirrhotic patients with acute variceal bleed (AVB) due to its vasoconstrictor effects. Ischemic complications are uncommon adverse events associated with worse outcomes. Case presentation We present a case of alcohol-related cirrhosis, who was started on terlipressin for AVB. However, he developed bilateral lower limb gangrene with ischemic skin necrosis and ultimately succumbed to death. Conclusion Although ischemic adverse events are uncommon with terlipressin, it is important to be aware of these complications as they may be severe and potentially life threatening.